2004
DOI: 10.2174/1568007043337535
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Adrenoceptors: A Major Drug Target in Neurological and Psychiatric Disorders?

Abstract: Considerable attention has recently been paid to astrocyte functions, which are briefly summarized. A large amount of data is available about adrenoceptor expression and function in astrocytes, some of it dating back to the 1970's and some of it very recent. This material is reviewed in the present paper. The brain is innervated by noradrenergic fibers extending from locus coeruleus in the brain stem, which in turn is connected to a network of adrenergic and noradrenergic nuclei in the medulla and pons, contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 438 publications
(563 reference statements)
0
65
0
Order By: Relevance
“…Astrocytes express Gq-linked, as well as Giand Gs-linked metabotropic receptors that are activated by norepinephrine, acetylcholine, serotonin, and likely other neuromodulators (Hertz et al 2004;Verkhratsky et al 2012). One of the characteristics of neuromodulators is that they typically target multiple cells via volume transmission and diffusion across considerable distances before receptor binding (Callado and Stamford 2000;Cragg et al 2001).…”
Section: Do Neuromodulators Act Through Astrocytes To Evoke Long-lastmentioning
confidence: 99%
“…Astrocytes express Gq-linked, as well as Giand Gs-linked metabotropic receptors that are activated by norepinephrine, acetylcholine, serotonin, and likely other neuromodulators (Hertz et al 2004;Verkhratsky et al 2012). One of the characteristics of neuromodulators is that they typically target multiple cells via volume transmission and diffusion across considerable distances before receptor binding (Callado and Stamford 2000;Cragg et al 2001).…”
Section: Do Neuromodulators Act Through Astrocytes To Evoke Long-lastmentioning
confidence: 99%
“…In addition to the SCN, reports also have demonstrated that NA generates circadian-clock oscillation in peripheral organs and cells (16,17). Thus, since various roles of NA and several types of adrenergic receptor expression in astrocytes have been reported (18), the possibility also exists that clock-gene expression in astroglial cells might be mediated by NA -adrenergic receptor cascades.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, downregulation of the astrocytic b 2 -AR-pathway might be involved into a number of neurological conditions such as multiple sclerosis, Alzheimer's disease, human immunodeficiency virus encephalitis, stroke and hepatic encephalopathy (reviewed in Hertz et al (2004) and Laureys et al (2010)). It has been recently reported however that b-AR stimulation together with TNF-receptor triggering may also induce synergistic IL-6 expression in astrocytes, an effect which warrants further investigation also in view of the role of uncontrolled expression of IL-6 in the CNS in neurodegeneration and glioma development (Spooren et al 2011).…”
Section: Astrocytesmentioning
confidence: 99%